Mutation of Mitochondrial DNA G13513A Presenting with Leigh Syndrome, Wolff-Parkinson-White Syndrome and Cardiomyopathy - Shi-Bing Wang; Wen-Chin Weng; Ni-Chung Lee; Wuh-Liang Hwu; Pi-Chuan Fan; Wang-Tso Lee (Elsevier, 2008)
Mutation of mitochondrial DNA (mtDNA) G13513A, encoding the ND5 subunit of respiratory chain complex I, can cause mitochondrial encephalopathy with lactic acidosis and stroke-like episodes (MELAS) and Leigh syndrome. Wolff-Parkinson-White (WPW) syndrome and optic atrophy were reported in a high proportion of patients with this mutation. We report an 18-month-old girl, with an 11-month history of psychomotor regression who was diagnosed with WPW syndrome and hypertrophic cardiomyopathy, in association with Leigh syndrome. Supplementation with coenzyme Q10, thiamine and carnitine prevented further regression in gross motor function but the patient's heart function deteriorated and dilated cardiomyopathy developed 11 months later. She was found to have a mutation of mtDNA G13513A. We suggest that mtDNA G13513A mutation is an important factor in patients with Leigh syndrome associated with WPW syndrome and/or optic atrophy, and serial heart function monitoring by echocardiography is recommended in this group of patients.